Superoxide chemistry revisited: synthesis of tetrachloro-substituted methylenenortricyclenes - Budanur, Basavaraj M.; Khan, Faiz Ahmed (Beilstein Journal of Organic Chemistry, 2014)
An unexpected reactivity of the superoxide ion leading to the synthesis of tetrachloroaryl/vinyl-substituted nortricyclenes through its dual mode of action has been reported. KO2 was found to be superior and the only reagent to perform this kind of reaction over other conventional bases. Addition of the antioxidant BHT (2,6-di-tert-butyl-4-methylphenol) improved the yields of methylenenortricyclenes. A complete deuterium incorporation was observed in the superoxide-mediated reaction in DMSO-d6. Friedel–Crafts acylation reactions of 3-methylenenorticyclenes yielded 2-propanone-substituted pentachloronorbornenes.
Keywords: BHT; dehydrohalogenation/rearrangement; Friedel–Crafts acylation; methylenenortricyclene; superoxide ion